THE ROLE OF THE GOVERNMENT IN COMMUNITY EMPOWERMENT THROUGH WASTE BANK MANAGEMENT - Saragi, Siswati; Sinaga, Kariaman; Purba, Budiman (Universitas Dharmawangsa Medan, 2020)
Garbage is a big problem in Medan City. Therefore, this study aims to find out how the role of government in empowering the community through waste management. In this study, data collection techniques were carried out through interviews, observation, and literature study. The analysis technique used is an interactive qualitative. Qualitative data analysis is carried out interactively and continues continuously until it is complete so that the data is already saturated. The results showed that the government did not have a special program for the development of this garbage bank. When the government has not optimally developed future development plans, the community will also feel pessimistic and unsure of the existence of this garbage bank. The community is less interested in getting involved in this garbage bank. The community felt that the training they had received was only knowledge and did not have a great opportunity to be developed. This relates to the statement that one of the obstacles in implementing community empowerment is the rejection of the community itself because the community does not have confidence.